Rural women in poverty : NGO interventions for alleviation - Salahuddin, Khaleda; Shamim, Ishrat (Dhaka : Women for Women, 1996)
Social science
Bibliogrphay : p. 212-214
1996-09-14
Keywords: Females; Poverty; Bangldesh